Pelatihan Penulisan Soal Pilihan Ganda Beralasan berbasis Higher Order Thinking Skill (HOTS) sebagai Alternatif Bentuk Evaluasi Hasil Belajar Siswa SD - Alfarisa, Fitri; Robiansyah, Firman; Sutarjo, Ajo; Safira, Nurul; Ardianti, Sylvia (Universitas Pendidikan Indonesia Kampus Serang, 2023)
Evaluation of learning outcomes in the form of multiple choices generally only measures Lower Order Thinking Skill (LOTS) abilities, namely: remembering, knowing and applying. Measuring student learning outcomes is not only LOTS, but also Higher Order Thinking Skill (HOTS). This requires a modified form of multiple-choice instrument. The aim of this service is to provide training in writing reasoned multiple choice questions based on HOTS and to determine the satisfaction of elementary school teachers at the UPI Serang Campus Laboratory after participating in the training activities. The method of this service is training, with two sessions, namely the first session providing material related to HOTS and the second session is a presentation and reflection on the results of HOTS questions made by elementary school teachers. This training activity consists of three stages, namely the preparation, implementation and evaluation stages. The results of the teacher satisfaction questionnaire regarding the training activities carried out showed that teachers gained very good knowledge of the material and satisfaction in terms of training facilities. This training can be used as a reference for increasing teacher capacity in developing HOTS-based questions in the future.